The Strandline Glacier (Northern Victoria Land, Antarctica). Variation of The ice-cliff margin 1987-1988. - BARONI, CARLO (1988)
A detailed geomorphological sketch map has been compiled on the basis of a topographic survey of the Strandline Glacier margin. Measurements made from survey stations during the field seasons 1986/87 and 1987/88 show a recession of the ice cliff of about 0.8 m. A glacier position measurement made by CHINN in Dec. 1984 (Ganovex IV) was repeated in Feb. 1988, showing an ice cliff retreat of 2.9 m since that time.